PERBANDINGAN TINGKAT KEPUASAN KELUARGA PASIEN GAWAT DARURAT DAN GAWAT NON DARURAT TERHADAP MUTU PELAYANAN KESEHATAN DI UGD RS. BAPTIS BATU - Kurnia, Erlin; Yusanto, Diba (Jurnal Penelitian STIKES Kediri, 2010)
BackgroundÂ Â Â : The differences of the satisfaction level among emergency and non emergency patient family become one of important problems in Emergency Unit Batu Baptist Hospital. The purpose of this research is for comparing the satisfaction level among emergency and non emergency patients family to the health service quality given by Emergency Unit at Batu Baptist Hospital.Â Â MethodÂ Â Â Â Â Â Â Â Â Â Â : this research was comparative study. The population are all of the patient family in Emergency Unit. The quantity of the sample are 100 respondences that was taken by accidental sampling. The independent variable is health service quality. The dependent variable was satifaction level of emergency and non emergency patient is family.The data was analized by â€œWilcoxon Testâ€ with mean level Â Â 0,05. The result of this research showed that there was no difference of satisfaction level between emergency and non emergency patients family. The result of statistic test â€œWilcoxonâ€ is p = 0,465 and p Â , so that H0 is accepted. Â ConclusionÂ Â Â Â Â : The conclusion of this research is the same satisfaction between emergency and non emergency patient family. It is very satisfy result so that the health service quality at Emergency Unit in Batu Baptist Hospital have been suitable with the patient and customer hopes.